Pengaruh Tingkat Perputaran Kas, Loan to Deposit Ratio, Tingkat Pertumbuhan Jumlah Nasabah, Spread Management dan Ukuran Perusahaan pada Profitabilitas Koperasi Simpan Pinjam - Akua Miyanti, Gusti Ayu Diah; Putra, I Wayan (E-Jurnal Akuntansi, 2012)
This study aims to examine the influence of cash turnover, LDR, the rate of growth of the number of customers, spread management and firm size on the profitability of Savings and Loan Cooperative in Badung regency period 2008-2010. The population of this research is all  Savings and Loan Cooperative in Badung regency which amount are 32. Tests performed with the classical assumption test followed by multiple linear regression test. Partially only cash turnover, the rate of growth in the number of customers and management spread a positive effect on the profitability of Savings and Loan Cooperative. LDR has no effect, while the negative effect of firm size. Suggestions for further research, are expected to use other independent variables to assess the profitability of the different objects.
Keywords: cash, ldr, customers, size, profitability